SIMULATION AND ANALYSIS OF COLLISION AVOIDANCE ALGORITHM ON UAV USING VELOCITY OBSTACLE METHOD - Natanael Lbn Toruan, Gopindo
The use of unmanned aircraft (UAV) in modern times is very much. As technology grows, more and more variations of UAV capabilities. The use of UAVs is now increasing by the rise of human needs both in civil and military fields. To avoid any obstacles in its path, UAVs must have the ability to avoid collisions. The problem of collision avoidance is to determine the probability of collision and maneuverability adjusted to the circumstances surrounding obstacles. In determining the maneuver, two methods of collision avoidance, namely the distance difference method and velocity obstacle method. In this research, the second method of comparison analysis using MATLAB software program that issued the simulation result which then produced the comparison graph of drift and timeloss to the turn rate of UAV. In order to speed up the actual conditions, the path passed by the UAV is set in the area of South Jakarta, where many skyscrapers meet the criteria as obstacles to the UAV used. After doing the simulation with variation of turn rate, then by using method of velocity obstacle has more effective than distance difference method.